Система послеаварийного мониторинга АЭС с использованием беспилотных летательных аппаратов: концепция, принципы построения - Саченко, А.А.; Кочан, В.В.; Харченко, В.С.; Ястребенецкий, М.А.; Фесенко, Г.В.; Яновский, M.Э. (Ядерна та радіаційна безпека, 2016)
Предложена концепция проектирования системы послеаварийного мониторинга оборудования и территории АЭС после тяжелой аварии с использованием беспилотных летательных аппаратов (БПЛА). Проводная сеть определена как наиболее уязвимая в ходе мониторинга аварий. В качестве основных характеристик системы рассматриваются информативность, живучесть и достоверность. Описываются меры по их обеспечению. Запропоновано концепцію проектування системи післяаварійного моніторингу обладнання та території АЕС після тяжкої аварії з використанням безпілотних літальних апаратів (БПЛА). Провідна мережа визначена як найбільш вразлива в ході моніторингу аварій. В якості основних характеристик системи розглядаються інформативність, надійність і достовірність. Описуються заходи щодо їх забезпечення. The paper presents a concept of designing the post-accident system for monitoring the equipment and territory of nuclear power plant after a severe accident based on unmanned aircraft vehicle (UAVs). Wired power and communications networks are found out as the most vulnerable ones during the accident monitoring, and informativity, reliability and veracity are recognized as system basic parameters. It is proposed to equip measurement and control modules with backup wireless communication channels and deploy the repeaters network based on UAVs to ensure the informativity. Modules possess the backup power battery, and repeaters appear in the appropriate places after the accident to provide the survivability. Moreover, an optimization of UAVs’ location is proposed according to the minimum energy consumption criterion. To ensure the veracity, it is expected to design the noise-immune protocol for message exchange and archiving and selfdiagnostics of all system components.